Evaluasi Kerusakan Lapisan Permukaan Perkerasan Lentur Pada Ruas Jalan Parit Bugis Kabupaten Kubu Raya dengan Metode Indeks Kondisi Perkerasan - Barokah, Juniwati; Eti Sulandari; Siti Mayuni (Jurnal Serambi Engineering, 2025)
This study was conducted on Parit Bugis Street, Sungai Raya, Kubu Raya Regency, West Kalimantan. This road has a role in the development of the Kubu Raya area, as evidenced by the existence of an industrial area around it. The increase in traffic that occurs on the road has resulted in various obstacles to damage to the road pavement surface which has an impact on the performance of the pavement structure. The damage that occurs on Jalan Parit Bugis is due to the slow handling of road surface damage. This study uses pavement condition analysis with the IKP PD-01-2016-B Guideline Method. Common damages include aggregate wear, holes, edge cracks, joint reflection cracks, slumps, longitudinal cracks and grain release caused by vehicle loads. The average pavement condition index is 29.31, categorized as very poor. The percentage of pavement conditions varies from good 16%, poor 17%, severe 30%, very severe 12% and destroyed 25%. The types of recommended handling include routine maintenance, periodic maintenance and reconstruction. The results of the study concluded that the pavement condition of Jalan Parit Bugis, Sungai Raya, Kubu Raya Regency, was very poor with various types of damage that affected its performance.